Uji Efektivitas Formulasi Sediaan Lipstik Menggunakan Bahan Pewarna Alami Dari Ekstrak Etanol Gambir (Uncaria Gambir (Hunteri)Roxb.) Dan Ekstrak Etanol Buah Stroberi (Fragaria Vesca). - Simorangkir, Delisma; Puspita, Rika; Harnis, Zola Efa (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Abstract: Lipstick is a form of lip coloring preparation which is a cosmetic preparation used to color the lips, to improve aesthetics in facial make-up. Lipstick preparations are available in various forms such as liquid, crayon, liptin, lipbam and cream. Lipstick consists of a coloring agent dispersed in a carrier made from a mixture of wax and oil, in such a composition as to provide the desired melting temperature and viscosity. The aim of the research is to determine the physical stability of lipstick preparations made from gambier extract and strawberry fruit extract as coloring agents. Sampling was carried out using a purposive sampling method, namely a random sampling methodology. The samples used were Gambir (Uncaria Gambir (Hunteri) Roxb.) and Ethanol Extract of Strawberries (Fragaria Vesca). then extracted by maceration using 96% ethanol solvent, concentrated by rotary. The combination of gambier ethanol extract and strawberry ethanol extract was formulated with a concentration of F1: 5%:5%, F2 :10%:10%. F315%:15%. Examination of the quality of the preparation includes organoleptic, homogeneity, pH, irritation, preference and continues with statistical analysis tests using One Way Anova. The results of normality tests with the Shapiro-Wilk test and homogeneity test, produce a value for each data > 0.05, so the data is normally distributed. The results of the One Way Anova test for each formulation group showed that the Sig value was <0.05, so the formulations had a significant difference.